Review of surgical anatomy of tubercle of Zuckerkandl and its importance in thyroid surgery - S Viveka (Wolters Kluwer Medknow Publications, 2018)
Background and Objectives: Tubercle of Zuckerkandl (TZ) is the posterior or posterolateral extension of thyroid gland. Recurrent laryngeal nerve (RLN) is related to TZ either on its posterior or posteromedial aspect in the deeper fascial plane. The objective of this review is to report separately the prevalence of TZ as noted by anatomists and surgeons. Materials and Methods: An extensive search for articles with TZ either in the title or keywords was done using PubMed, ScienceDirect, Google Scholar, SciELO, EMBASE, and Web of Science databases. The search terms were restricted to TZ, Zuckerkandl tubercle, posterolateral extension of thyroid, RLN, and thyroid surgeries. Results: Out of 39 records, 25 studies, reported total number of sides where TZ was studied with prevalence percentages (n = 4231 sides). This included 6 cadaveric studies and 19 surgical studies. Combined pooled prevalence of TZ was found to be 76.5%. Prevalence in cadaveric and surgical studies was 84% and 69%, respectively. Overall, 15 studies reports RLN is related to posterior or posteromedial to TZ. Conclusions: The prevalence of TZ is 76.5%. When present, it is a useful guide for locating, dissecting, and preserving RLN. Cadaveric studies report a higher prevalence of 84%, while surgical studies report an average of 69% TZ. Most surgical studies report higher right-sided prevalence.